Estudio de prefactibilidad para el montaje de un sistema de franquicias para el restaurante La Spaghettata en Bogotá - Orjuela, Daniel; Fragozo, Orlando; Andrade, Andrea; Caicedo, Yuri (Escuela Colombiana de Ingeniería Julio Garavito, 2017)
The present document contains the pre-feasibility study for the installation of the franchise system of the restaurant La Spaghettata in Bogotá. It is mainly sought to make the business increase under the franchise mode and take advantage of the boom that this system is currently having in the country and in South America. It is proven that this modality of growth is currently the most effective and the lowest risk of failure, so it is a matter of replicating a successful business. The information collected to carry out this report comes from the restaurant La Spaghettata and another part is obtained from secondary information as Internet sources and specialized magazines.

El presente trabajo de grado contiene el estudio de prefactibilidad para el montaje del sistema de franquicias del restaurante La Spaghettata en Bogotá. Se busca principalmente hacer crecer el negocio bajo la modalidad de franquicias y aprovechar el auge que este sistema está presentando actualmente en el país y en Suramérica. Está comprobado que esta modalidad de crecimiento es actualmente la más efectiva y la que menor riesgo tiene de fracaso, pues se trata de replicar un negocio exitoso. La información recolectada para llevar a cabo este informe proviene del restaurante La Spaghettata y otra parte se obtuvo de información secundaria como fuentes de internet y revistas especializadas.
Keywords: Franquicias ( Comercio minorista); Mercado de exportación; Franchising (Retail); Export market